Juridical Analysis of the Etawaku Trademark Cancellation in Business Cooperation - Tsani, Sulthan Mada Maulana; Indrawati, Septi (Jurnal Hukum Magnum Opus, 2025)
Brand is an important component in a business. Trademarks have the power to shape a company's image and influence consumer decisions. Nevertheless, there are registered trademarks with similarities or similarities with previously registered trademarks and the first registrant feels disadvantaged, so that legal efforts can be made to cancel the trademark, remove the trademark, or apply for compensation. This study aims to determine how the consequences of cancellation of the trademark against business cooperation agreements, to achieve these objectives can be done through the method of normative legal research with more emphasis on understanding in obtaining answers by basing on the principles and principles of law applied to regulate the sovereignty of a country. The results show that the cancellation of the "ETAWAKU" Trademark can affect business cooperation in a significant way, considering that the brand is an important element in marketing and selling products. Where the impact can be in the form of contract cancellation, economic loss, or reputational damage for the parties involved. Therefore, it is very important to ensure that the trademark used in business cooperation has strong and valid legal protection, and anticipate the possibilities that can arise due to the cancellation of the trademark.